The "hot hand" reconsidered: A meta-analytic approach - Avugos, S.; Köppen, J.; Czienskowski, U.; Raab, M.; Bar-Eli, M. (Psychology of Sport and Exercise, 2013)
Objectives: Extensive searches for the "hot hand" have been performed in a variety of sports since the pioneering study of Gilovich, Vallone, and Tversky (1985), but empirical evidence for the existence of the effect is still fairly limited. The current review reconsiders the hot hand in sports using a meta-analytic approach.